MASTERY OF THE CONCEPT OF GLOBAL WARMING WITH SEARCH, SOLVE, CREATE AND SHARE LEARNING MODEL INTEGRATED MIND MAPPING - Cahyani, Dina; Yennita, Yennita; Syahril, Syahril (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
Search, Solve, Create, and Share is a learning model that guides students to the process of solving problems. With this Search, Solve, Create, and Share learning model, students can train creative thinking skills to be able to expand or search for ideas independently. This study was conducted to see the difference in mastery of the concept of students who use the Search, Solve, Create, and Share learning model and conventional learning on global warming material. This study was designed with Posttest-Only Control Design. The samples used were class XI IPA 1 as an experimental class with an integrated Search, Solve, Create, and Share learning model Mind Mapping and XI IPA 2 as a control class with conventional learning. The results of the t-test show that there are differences in mastery of the concepts of students who apply the Search, Solve, Create, and Share learning model integrated with Mind Mapping with control classes that apply conventional learning.. The conclusion of this study is that there are differences in mastery of the concepts of students who apply the Search, Solve, Create and Share learning model integrated with Mind Mapping with students who apply conventional learning, and mastery of the concepts of students who apply the Search, Solve, Create, and Share learning model better than the control class with conventional learning.